Strategi dan Saluran Pemasaran Rengginang Lorjuk Produksi Desa Prenduan - Hopid, Hopid (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2023)
Rengginang lorjuk is one of the many typical snacks of Sumenep which is very famous, the marketing of rengginang lorjuk has penetrated outside the area marketed by marketing institutions, namely large merchants, and retailers to meet consumer demand. The high demand for rengginang lorjuk is due to the taste, aroma, and ingredients used being very preferred by consumers compared to rengginang produced outside the Sumenep area. The purpose of this study was to analyze effective marketing strategies and channels. This research method uses a qualitative descriptive approach to examine marketing strategies and channels with the object of research producers and marketing institutions in Prenduan Village. Primary data collection used observation and interview methods while secondary data were obtained from literature studies related to this study. The results showed that the marketing strategy applied by producers is product strategy, cooperation strategy, and price strategy. The marketing channel for the first Prenduan Village production is from producer to wholesaler to retailer then consumer, second from producer to retailer to retailer then consumer, third from producer to retailer then consumer, and fourth from producer to retailer then consumer.